Gestational exposure to particulate matter from urban wildfires is associated with changes in circulating oxylipins but not flame retardants 7 to 13 months post-exposure - Eunyoung Park; Qing Shen; Zhichao Zhang; Claire E. O’Brien; Amanda J. Goodrich; Elizabeth E. Angel; Irva Hertz-Picciotto; Daniel J. Tancredi; Sean Raffuse; Deborah H. Bennett; Rebecca J. Schmidt; Ameer Y. Taha (Environment International)
Exposure to fine particulate matter (PM2.5) from wildfire smoke has been linked to immune dysregulation underlying multiple health conditions, but data on the long-term effects of these exposures during gestation are lacking. Smoke PM2.5 from wildfires occurring in urban areas is of particular concern because it can carry persistent chemicals within household furniture or soil, as well as polyaromatic hydrocarbons (PAHs) from combusted materials. The present study investigated the long-term associations between wildfire PM2.5 and serum polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), PAHs and lipid mediators (i.e., oxylipins) involved in immune regulation in participants from the B-SAFE (Bio-Specimen Assessment of Fire Effects) study, which enrolled women pregnant during or shortly after the 2017 Tubbs Fire in California (n = 140). Serum samples were collected and assayed 7 to 13 months post-exposure, at which point 20 women were still pregnant and 120 women were postpartum. Adjusted linear regression models revealed a significant positive association between increasing PM2.5 (μg/m3) exposure and serum concentrations of benzo[k]fluoranthene, a PAH (β = 0.866, P = 0.0403, [95 %CI: 0.0389, 1.69]). No significant associations were observed between PM2.5 exposure and serum PBDEs, PCBs or other PAHs. Increased exposure to PM2.5 was associated with lower serum concentrations of lipoxygenase (LOX)-derived free oxylipins and increased concentrations of LOX-derived oxylipins esterified to circulating lipids. These findings provide new evidence of long-term effects of gestational wildfire PM2.5 exposure on serum benzo[k]fluoranthene levels and the turnover of oxylipins involved in immunity via the LOX pathway. Additional studies are warranted to better understand the impact of these changes on maternal and child health.